Dietary tryptophan and the risk of obesity and type 2 diabetes: Total effect and mediation effect of sleep duration. Issue 2 (27th January 2022) - Wang, Weiqi; Wang, Xinyue; Liu, Lin; Liu, Zengjiao; Han, Tianshu; Sun, Changhao; Yang, Xue
Abstract: Objective: The aims of this study were to examine the effects of tryptophan consumption on obesity and type 2 diabetes (T2D) risk and whether sleep duration mediates these effects. Methods: Overall, data of 7, 908 participants were obtained from the China Health and Nutrition Survey (1997‐2011). A total of 6, 373 and 4, 398 participants who reported sleep duration and had blood samples, respectively, were incorporated into subgroup analyses. Multivariate Cox regression models were used to assess the associations between tertiles of tryptophan intake with obesity and T2D. General linear regression models were used to evaluate the effect of tryptophan on sleep time and plasma biomarkers. Results: Dietary tryptophan was significantly associated with decreased risk of obesity and T2D risk (hazard ratio tertile 3 to tertile 1 : 0.602 [95% CI: 0.500‐0.724]; 0.693 [95% CI: 0.565‐0.850]). Sleep duration was significantly higher, and hemoglobin A1c, total cholesterol, low‐density lipoprotein cholesterol, and apolipoprotein B‐100 (APO‐B) were lower in the high tertile of tryptophan compared with the low tertile ( p < 0.05). In addition, mediation effects on the associations of tryptophan intake with obesity and T2D risk were observed for sleep duration (estimated mediation percentage: 31.902% and 37.391%). Conclusions: Dietary tryptophan showed advantageous effects on obesity and T2D risk. Furthermore, sleep duration potentially mediated for these effects.